Impact of cooking method on phenolic composition and antioxidant potential of four varieties of Phaseolus vulgaris L. and Glycine max L. (April 2019) - Teixeira-Guedes, Catarina I.; Oppolzer, David; Barros, Ana I.; Pereira-Wilson, Cristina
Abstract: The present study aimed to investigate the effects of different cooking conditions - atmospheric (100 °C) and pressure cooking (115 °C) - on the phenolic composition and antioxidant activity of methanolic extracts of four Phaseolus vulgaris varieties and soy ( Glycine max ). Contrary to soy, in P. vulgaris varieties both cooking methods increased drastically the total phenolic, flavonoid, and ortho -diphenol content, as well as antioxidant capacity. These results were corroborated by HPLC analysis, where an overall increase of phenolic acids and flavonoids was detected in processed samples. However, draining the cooking water significantly decreased phenolic acids, flavonoids and antioxidant activity in all P. vulgaris varieties and as well as soy. The hypothesis that cooking increases the compound accessibility and nutritional value through increased release of phytochemicals was verified in the present study for P. vulgaris varieties. Keeping the cooking water is crucial to the increased nutritional value of all Phaseolus varieties. Overall, compared with the tested varieties of Phaseolus, soy, to which many health benefits are attributed, is not the best legume source of antioxidants. Highlights: Cooking improved phytochemical composition and antioxidant activity of common beans. Raw soy had higher phenolic content but cooking increased isoflavones in extracts. Draining the cooking water drastically decreased phenolic content and antioxidant activity.